(untitled) (Proceedings of The International Conference on Economics and Development, 2019)
With urbanization and expansion of cities, India witnesses a dramatic growth in its buildings sector. These conventional buildings are responsible for significant consumption of fossil fuel energy and rise of global warming. According to the U.S. Energy Information Administration (EIA), the largest building energy consumption will be in India by the year 2040. Thus, it becomes necessary to incorporate technological ameliorations like green buildings. Benefits of green buildings are not restricted to energy sector only, but they are known to have positive health impacts on its occupants. Various studies claim the higher productivity of workers inside green offices leads to higher benefits in the long run. Realizing the role of green buildings in sustainable development of a country, India has set up Indian Green Building Council (IGBC). Despite being environmentally benign, the construction of green buildings in developing nations like India comes with its own economic challenges. Due to involvement of upcoming sophisticated technologies, the construction cost involve is high. Rate of growth of green buildings in India is sluggish in comparison to other developed nations. Limited land area in India demands replacement of old conventional buildings with new green ones which is further surrounded by related issues. In this paper, we aim at to analyze the development of affordable green buildings, their growth and highlight various opportunities in this field along with the practical challenges at various levels involved with respect to Indian scenario. We also provide a comparative analysis of green buildings and conventional buildings and finally suggest appropriate measures for affordable and sustainable development of green buildings.